2014
DOI: 10.1186/1472-6831-14-80
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vitroperiodontal biofilm model for assessing antimicrobial and host modulatory effects of bioactive molecules

Abstract: BackgroundInflammation within the oral cavity occurs due to dysregulation between microbial biofilms and the host response. Understanding how different oral hygiene products influence inflammatory properties is important for the development of new products. Therefore, creation of a robust host-pathogen biofilm platform capable of evaluating novel oral healthcare compounds is an attractive option. We therefore devised a multi-species biofilm co-culture model to evaluate the naturally derived polyphenol resverat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 35 publications
1
67
1
2
Order By: Relevance
“…Broths used were Schaedler’s Anaerobic broth (SCH), BHI and Tryptic Soy broth (+0.8% w/v glucose and 0.6% w/v yeast extract; TSB). In maintaining and building up the 10-species biofilms, the medium Artificial Saliva (AS) was exclusively used [16]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Broths used were Schaedler’s Anaerobic broth (SCH), BHI and Tryptic Soy broth (+0.8% w/v glucose and 0.6% w/v yeast extract; TSB). In maintaining and building up the 10-species biofilms, the medium Artificial Saliva (AS) was exclusively used [16]. …”
Section: Methodsmentioning
confidence: 99%
“…Ten-species biofilms were built up on Thermanox coverslips as detailed elsewhere [16, 19] in the following order: an initial 3-species biofilm consisting of S . mitis , S .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymicrobial communities are able to form biofilms upon this vast variety of substrates [5••, 6, 7]. It is now generally well understood that dental plaque biofilms contain many resident species that modulate one another, their environment, and also the host response [8][9][10]. Despite the widely acknowledged presence of yeasts within the oral cavity, their active role and participation in oral diseases is generally perceived to be restricted to mucosal-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Some species are potentially beneficial, contributing to a healthy oral homeostasis, while others are associated with various stages of gingivitis and periodontitis, potentially acting as keystone species and/or virulent components of the disease-inducing microbiota (6). Studies with pure cultures, defined communities in vitro, and animal models have revealed proinflammatory characteristics and interspecies signaling that result in community shifts and a host response leading to tissue destruction (15,16). However, approximately one-third of the oral microbial species-level taxa are still uncultured, including dozens of diseaseassociated lineages (17).…”
mentioning
confidence: 99%